The impact of travel time reliability and perceived service quality on airport ground access mode choice - Mei-ling Tam; William H. K. Lam; Hing-po Lo (Journal of Choice Modelling, 2011)
This study makes two contributions to existing airport ground access mode choice models. The first is an assessment of travel time reliability on air passenger airport ground access mode choice decisions. Revealed preference questions were asked to determine the safety margin allowed for ground access journey to airports. The larger the safety margin allowances, the less reliable the passenger perceived the mode to be. Stated preference questions were also used to determine the impact of travel time reliability on mode choice decisions. The second contribution of this research is the incorporation of air passenger perceived service quality in the calibration of airport ground access mode choice model. With the use of the survey data, the effects of safety margin allowances, travel time reliability, and perceived service quality on ground access mode choices to Hong Kong International Airport are quantified by a multinomial logit-type mode choice model. For strategic planning, the calibrated model can be used by the airport authority and various transport operators for evaluating the changes in the service attributes on modal split pattern in international airports, hence improving the access mode services.
Keywords: 330; ground access; mode choice; perceived service quality; safety margin; travel time reliability